Pantun: Satu nama beda nasib - Rusyana, Enang; Rohmah, Utami Nur (Universitas Mulawarman, 2025)
In Indonesian literature, two distinct regional works share the same name: pantun. These are the Indonesian pantun and the Sundanese pantun. Despite their shared nomenclature, the survival of these two forms has diverged significantly: Indonesian pantun thrives, while Sundanese pantun is nearly extinct. This study aims to describe several aspects suspected to be the cause of the inequality in survival between Indonesian and Sundanese pantun. Employing a qualitative descriptive method with purposive sampling, data on both pantun types were gathered, analyzed, and discussed using relevant theories related to each form. The research found that the differences stem from variations in type, structure, function, teaching methods, teaching materials, and everyday usage. Indonesian pantun is a form of bound poetry with a simple structure, serves various non-ritual functions, is taught across all schools in Indonesia, and is actively practiced in daily life. In contrast, Sundanese pantun blends prose and poetry, possesses a complex structure, is tied to specific rituals, is only taught in senior high schools in West Java, and is no longer part of everyday life. Consequently, many Sundanese people are unfamiliar with it. The study highlights how these contrasting factors have contributed to the divergent fates of the two pantuns.